P326 COVID-19 pandemic and alcohol-specific hospital admissions. (19th June 2022) - Subhani, Mohsan; Sheth, Abhishek; Sahota, Simon; Ryder, Stephen
Abstract : Introduction: Alcohol related mortality during pandemic has been reported highest since 2001. Tertiary care hospital in England have observed an increase in admissions for ArLD. We aim to describe the effect of the Covid-19 pandemic on hospital admissions for wholly alcohol attributable conditions. Method: This retrospective cohort study was conducted at Nottingham University Hospitals (NUH) (approval ID 21-502C). Cohorts were defined as pre-pandemic (March-2019 to February-2020) and pandemic (March-2020 to February-2021). Conditions were defined as alcohol specific where alcohol was the sole cause, and their alcohol attributable fraction was 1.0 (100 per cent) (PHE 2020). Adult patients admitted to NUH with alcohol specific primary diagnoses during the two study periods were included. Descriptive comparisons were made between the groups with respect to alcohol specific primary diagnosis, liver-specific primary diagnosis, gender, age, ethnicity, civil status, length of stay and socioeconomic background. Results: A total of 255, 824 patients were admitted to NUH during the two study periods (pre-pandemic n=131, 022 and pandemic n=124802). of them 1484 patients had an alcohol specific primary diagnosis and were included in final analysis. Pandemic, compared to pre-pandemic, had a significantly higher number of alcohol specific admissions (811-vs-673, p<0.0001) and underlying alcohol related liver disease (549-vs-423, p=0.05). Patients admitted during the pandemic compared to pre-pandemic had a significantly longer length of stay and had a significant higher variation in socioeconomic background. Patients admitted during the pandemic were more likely to be in a relationship (p<0.01). There was no significant difference in mean age (p=0.92), sex (p=0.25) and ethnicity (p=0.08) between the two cohorts ( table 1 ). Conclusion: Although during the Covid-19 pandemic total number of hospital admissions reduced a significantly higher number of patients were admitted due to an alcohol specific condition and had underlying liver disease. Patients admitted during the pandemic had a longer length of stay and observed extreme variation in socioeconomic background.